2010
DOI: 10.1039/b925407b
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation rheology of the vitreous: mechanical properties of biological tissue

Abstract: We demonstrate the importance of measuring the mechanical properties of biological tissue in vivo by quantifying the mechanical properties of bovine vitreous both in its native state and upon removal from the eye. The mechanical properties are determined by the cavitation rheology technique developed in our labs to determine the linear modulus. This technique involves inducing a cavitation event at the tip of a syringe that is located at an arbitrary location within the vitreous sample. The pressure at which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 25 publications
3
74
1
Order By: Relevance
“…Additionally, the reported studies involved the dissection of the eye and the removal of the vitreous humor, processes that drastically alter its biomechanics. Recently, [9] used an insertable probe for measurements in an intact eye cavity, Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the reported studies involved the dissection of the eye and the removal of the vitreous humor, processes that drastically alter its biomechanics. Recently, [9] used an insertable probe for measurements in an intact eye cavity, Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been developed to measure the mechanical properties of the vitreous humor: nuclear magnetic resonance imaging for the liquefaction of the vitreous [10]; dynamic mechanical measurements with compression [11]; the relaxation of the scattering pattern in the human eye [12]; radiation force [13]; bulk measurements using cleated tools [14]; cavitation rheology [15]; and ultrasound image velocimetry [16]. Researchers qualitatively measured phenomena related to physiological changes in the eyes [10]–[12].…”
Section: Introductionmentioning
confidence: 99%
“…The shear storage moduli of the porcine vitreous ranged from 2.8 to 10 Pa [14]. Most recently, in vivo measurements of the mechanical properties of the vitreous humor were performed using the relationship between the applied pressure and the size of cavitation bubbles at the needle tip [15]. The results showed that the storage moduli of bovine vitreous were between 120 and 660 Pa [15].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 It is an inexpensive, fast, and portable method that estimates the elastic modulus by measurement of the critical pressure (P c ) required for internal cavitation. Cavitation is induced by air pumped through a needle inserted into the sample.…”
Section: 10mentioning
confidence: 99%
“…The first is that because the analysis assumes a neo-Hookean strain energy function, cavitation rheometry has only been used to characterize materials that are elastic solids. 11,12,[16][17][18][19] To extend this method to viscoelastic materials, the assumption of neo-Hookean mechanics must be examined relative to their rheological behavior. The second limitation is that Eqs.…”
mentioning
confidence: 99%